De-institutionalising the mad: Barham, P (1992) Closing the asylum. London: Penguin. - Pillay, Anthony L (PINS-Psychology in Society, 2026)
Peter Barham is a psychologist working in Britain, and writes from his experiences in that part of the world while also providing references to other western mental health systems. The book presents a critical analysis of the issue of psychiatric institutionalization as well as recent, and even earlier attempts at de institutionalization. There is evidence of extensive research, providing information from different sides of the deinstitutionalization issue.